Pengaruh Motivasi Belajar terhadap Prestasi Belajar Siswa pada Mata Pelajaran Ekonomi Bisnis di Sekolah Menengah Kejuruan Muhammadiyah 2 Pekanbaru - Mia Salmiah; Yulia Novita; Novia Rahmawita (UIR Press, 2021)
This research aimed at knowing the influence of students’ extrinsic learning motivation toward their learning achievement on Business Economics subject at Vocational High School of Muhammadiyah 2 Pekanbaru. This research was instigated by students who could not reach the minimum standard of passing grade, so their learning achievement was not yet maximum. It was a quantitative research. The subjects of this research were the eleventh-grade students of Accounting 1 and 2 and Marketing. Questionnaire and documentation were the techniques of collecting data. The technique of analyzing the data was simple linear regression test. Based on the research findings, it could be concluded that there was a significant influence of students’ extrinsic learning motivation toward their learning achievement on Business Economics subject at Vocational High School of Muhammadiyah 2 Pekanbaru. It was proven by the comparison between robserved and rtabel, it was obtained that robserved was higher than rtabel at 5% and 1% errors (0.202<0.664>0.263), so H0 was rejected and Ha was accepted. The contribution of the influence of students’ extrinsic learning motivation toward their learning achievement was 44.1%, and the rest (100%-44.1%=55.9%) was influenced by other factors that were not discussed in this research.